SuarAman Inovasi Platform Dukungan Psikologis Daring Berbasis Anonimitas bagi Mahasiswa Universitas Negeri Malang - Adinda Arofah Putri Indarti; Abdul Aziz Tri Nugroho; Alfia Nuraini; Alfi Nur Hayati; Aulia Nadia Majid; Azzahra Rahmalia Putri; Desta Awwallillah Zain; Bilbinia Herlinda Kuncoro Putri (INDO PUBLISHING, 2025)
In the Indonesian higher education context, student psychological well-being is a critical concern, particularly post-pandemic. This quantitative study designed SuarAman, an anonymous online psychological support system for Universitas Negeri Malang students. Using a User-Centered Design approach with 50 participants, data revealed 74% demanded anonymous platforms, while 88% considered anonymity essential for mental health support. The anonymous